Experience of International Air Transportation and Subsequent Lung Transplant in a Patient with COVID-19-associated Acute Respiratory Distress Syndrome: a Case Report - Oh, Dong Kyu (J Korean Med Sci, 2021)
We report an inspiring case of a 55-year-old Korean female diagnosed with coronavirus disease 2019 (COVID-19)-associated acute respiratory distress syndrome (ARDS) in Mexico. The patient was assessed for lung transplant as a salvage therapy for treatment-refractory ARDS following no signs of clinical improvement for > 7 weeks, despite best treatment. The patient was transported from Mexico to Korea by air ambulance under venovenous extracorporeal membrane oxygenation (ECMO) support. She was successfully bridged to lung transplant on day 88, 49 days after the initiation of ECMO support. ECMO was successfully weaned at the end of operation, and no bleeding or primary graft dysfunction was observed within the first 72 hours. The patient was liberated from mechanical ventilation on postoperative day 9 and transferred to the general ward 5 days later. Despite the high doses of immunosuppressants, there was no evidence of viral reactivation after transplant. At 3 months post-transplantation, she was discharged to home without complication. Our experience suggests that successful lung transplant for COVID-19-associated ARDS is feasible even in a patient with prolonged pre-transplant ECMO support. Lung transplant may be considered a salvage therapy for COVID-19-associated ARDS that does not respond to conventional treatments.